KONFLIK KEPENTINGAN DALAM KEBIJAKAN REKLAMASI KAWASAN TELUK BENOA PROVINSI BALI Kajian tentang Konsep Tri Hita Karana - Made Dwi Astika Tajem; Nur Saribulan (Fakultas Politik Pemerintahan IPDN, 2019)
Conflict of Interest in the Reclamation Policy of the Benoa Bay Area in Bali Province. Study of the Concept of Tri Hita Karana. This study aims to analyze the occurrence of conflicts of interest in the reclamation policy of the Benoa Bay area which is associated with the traditional development concept of Tri Hita Karana. This study uses a qualitative approach with descriptive method. Data is collected through interviews, observation, and documentation. In determining the informants used purposive techniques and snowball sampling. To analyze the data used Fisher’s theory, with the stages of data collection, data reduction, data presentation and drawing conclusions. The results showed that there was still a conflict of interest between the government, the private sector and the community in the Benoa Bay reclamation policy. Conflict of interest occurred because of the issuance of Presidential Regulation No. 51 of 2014 which was deemed not in accordance with several laws and regulations, Regional Regulation (Perda) in Bali, and the development concept of Tri Hita Karana. Conflict resolution efforts have been carried out by the government but are considered to be less than optimal. Keywords: reclamation, conflict of interest, tri hita karana